Keratin 17 Promotes T Cell Response in Allergic Contact Dermatitis by Upregulating C–C Motif Chemokine Ligand 20 - Luo, Yixin; Zhu, Zhenlai; Li, Bing; Bai, Xiaocui; Fang, Hui; Qiao, Pei; Chen, Jiaoling; Zhang, Chen; Zhi, Dalong; Dang, Erle; Wang, Gang (Frontiers in Immunology, 2022)
Allergic contact dermatitis (ACD) is a delayed-type hypersensitivity response to skin contact allergens in which keratinocytes are critical in the initiation of early responses. Keratin 17 (K17) is a cytoskeletal protein inducible under stressful conditions and regulates multiple cellular processes, especially in skin inflammatory diseases; however, knowledge regarding its contribution to ACD pathogenesis remains ill defined. In the present study, we clarified the proinflammatory role of K17 in an oxazolone (OXA)-induced contact hypersensitivity (CHS) murine model and identified the underlying molecular mechanisms. Our results showed that K17 was highly expressed in the lesional skin of ACD patients and OXA-induced CHS mice. Mice lacking K17 exhibited alleviated OXA-induced skin inflammation, including milder ear swelling, a reduced frequency of T cell infiltration, and decreased inflammatory cytokine levels. In vitro, K17 stimulated and activated human keratinocytes to produce plenty of proinflammatory mediators, especially the chemokine CCL20, and promoted keratinocyte-mediated T cell trafficking. The neutralization of CCL20 with a CCL20-neutralizing monoclonal antibody significantly alleviated OXA-induced skin inflammation in vivo. Moreover, K17 could translocate into the nucleus of activated keratinocytes through a process dependent on the nuclear-localization signal (NLS) and nuclear-export signal (NES) sequences, thus facilitating the activation and nuclear translocation of signal transducer and activator of transcription 3 (STAT3), further promoting the production of CCL20 and T cell trafficking to the lesional skin. Taken together, these results highlight the novel roles of K17 in driving allergen-induced skin inflammation and suggest targeting K17 as a potential strategy for ACD.